Pineapple “fusariose": incidence in fruit according to the time of harvest - Matos, Aristoteles Pires de; Sanches, Nilton Fritzons; Cunha, Getúlio Augusto Pinto da; Reinhardt, Domingos Haroldo R.C. (Pesquisa Agropecuaria Brasileira, 2014)
Observations on the development of "fusariose" in commercial plantations of pineapple were carried out for two years. The heaviest losses, due to Fusarium moniliforme var. subglutinans, occurred in the months of August and September, while the mildest ones, from May to July.